2020
DOI: 10.1039/c9fo01346f
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen promotes the migration and myogenic differentiation of C2C12 myoblastsviathe release of interleukin-6 mediated by FAK/NF-κB p65 activation

Abstract: Type I collagen has the potential to promote the migration and differentiation of C2C12 myoblast via IL-6 release that was mediated by FAK/NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…A similar nature of research is reported by the same author, but with a different research group [63], about the effects of collagen Type I on cell migration and differentiation through the culturing of mouse C2C12 myoblasts for skeletal muscle regeneration. The collagen I increases the production of interleukin-6 using nuclear factor κB (NF-κB) p65 that results in the myogenic differentiation of C2C12 cells in the cultured assay [63].…”
Section: Biosynthesis and Culturing For Type Isupporting
confidence: 59%
“…A similar nature of research is reported by the same author, but with a different research group [63], about the effects of collagen Type I on cell migration and differentiation through the culturing of mouse C2C12 myoblasts for skeletal muscle regeneration. The collagen I increases the production of interleukin-6 using nuclear factor κB (NF-κB) p65 that results in the myogenic differentiation of C2C12 cells in the cultured assay [63].…”
Section: Biosynthesis and Culturing For Type Isupporting
confidence: 59%
“…There was also no difference in the growth of C2C12 on different coating substrates, suggesting that pregel solutions from different layers of the bladder did not affect the growth of C2C12 cells. Myogenesis of the C2C12 was confirmed using the following criteria: Upon initiation of differentiation, the cells elongate, adhere, and fuse into multinucleated myotubes that express muscle-specific markers such as myosin heavy chain (MyHC) and myogenic regulatory factors such as myogenin in the terminal differentiation state [25]. As can be seen from the immunocytochemistry study (Figure 7A,B), the C2C12 fused into multinucleated cells on bladder ECM-coated substrates as efficiently as on commercial collagen type I.…”
Section: Effect On C2c12 Myogenic Differentiationmentioning
confidence: 99%
“…It was shown that high level of TNFα may cause apoptosis of myoblasts and myocytes, thus causing muscle atrophy [52]. Previous studies have shown that collagen I influences the migration and differentiation of myoblasts through regulating release of IL-6 [9]. Gelatin has also been shown to regulate production and secretion of IL-6 and TNFα in differentiated U937 lymphoma cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillar collagen I, the main component of ECM, distributes widely in endomysium, perimysium and epimysium, not only exerting biomechanical support but also influences the biological function of muscle cells [6,7,8]. Although it is known in vitro that collagen I promotes myogenesis of C2C12 myoblasts [9], muscle regeneration in vivo is known to be accompanied by a temporary and local breakdown of collagen, producing a mixture of collagen polypeptides without triple-helicity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation